The importance of writing, style and text editing in determining the credibility of monuments to Polish law in the work of Antoni Zygmunt Helcel (19th century - Pałucka-Czerniak, Iwona (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The observation of the scientific discourse related to the history of the Polish language, and more specifically the history of law, has become the general research goal of the article. Research interest is associated with the problem of the state and changes in linguistic awareness within a specialized communicative community. The analysed material is located on the border of two types of evidence that can constitute the basis for recreating the image of linguistic awareness: direct and indirect. A.Z. Helcel, a historian, by analysing old documents of Polish law written in Latin, gave an expression of a shaped and developed linguistic awareness. He introduced new proposals of research methods to the scientific discourse of legal historians, based on, among other things, linguistic analysis. He used a large repertoire of rhetorical and stylistic concepts to document the authenticity, antiquity and significance of a document. He called for attention to be paid to the stylistic formations considered by others to be trivial. He understood, distinguished and repeatedly used the terms: text, style, content, form, error, writing manner, habit. Most likely, he distinguished a functional style and an individual style. He understood the concept of a genre: he named various genres, mainly legal texts, and talked about genre-creation. He referred to the concept of a norm. He also noticed the need to simplify the graphy, i.e. he declared the use of transcription. He also included past Old Polish translations in the work, seeing them as a historical and historical-linguistic value. He was aware of the value of the old monuments of the Polish language, preserved in old translations.